Development of Enzyme Production Technology with Double Protease Immobilization Method (Calotropin and Papain) - Witono, Yuli; Masahid, Ardiyan Dwi; Belgis, Maria; Jayanti, Puja Dwi; Wahyuni, Livia; Giyarto, Giyarto (Indonesian Food Science and Technology Journal, 2025)
Abstract—Enzymes are biocatalysts widely applied in agriculture, food processing, chemical industries, and medical fields. Enzymes can be used singly or immobilized within a matrix. However, free enzymes often exhibit lower stability compared to immobilized enzymes. Therefore, this research aimed to evaluate the combined two proteolytic enzymes for extracting protein hydrolysates. The objective was to analyze enzymes' immobilization characteristics using carrageenan and determine the optimal concentration combination. Calotropin and papain were applied at concentrations of 2.5 mL, 3.5 mL, and 4.0 mL, respectively. The analysis parameters included yield, enzyme activity, soluble protein content, specific enzyme activity, stability, and kinetic parameters (Km and Vmax). The results showed that the combined proteases exhibited yields ranging from 44.43% to 48.63%; enzyme activities of 9.23–53.63 U/mL; soluble protein contents of 2.40–2.89 mg/mL; and specific enzyme activities of 3.54–18.62 U/mg protein. The enzymes were maintained stability at temperatures ranging from 30 to 60 °C. The kinetic parameters were determined as Km = 0.0034 g/mL and Vmax = 17.094 U/min.